NEW DATA ON URANIUM-BEARING VOLCANIC GLASSES - Levin V.N.; Boyarskaya R.V.; Belova L.N. (My University, 1990)
In the last decade, volcanic glasses have received considerable attention as possible sources of uranium mineralization. This idea is based on the hypothesis that volcanic glasses are very close in composition to the melt from which they solidified. The concentration of uranium is usually higher in volcanic glasses than in crystalline rocks. Based on this, it is suggested that the concentration of uranium in glasses corresponds to the concentration in the magmatic melt. The amount of uranium liberated during recrystallization of glasses can become a source of uranium in hydrothermal systems. The study of volcanic glasses enriched in uranium and of the products of recrystallization of these glasses supports the above conclusion. Radiographic analysis of these glasses reveals a homogeneous distribution of uranium. Results indicate that volcanic glasses are susceptible to certain changes with time. These changes can also have important influence on the concentration of uranium in them.